Assessing a multidimensional model of police legitimacy in South Korea with latent class analysis - Lee, Yung Hyeock (Journal of crime and justice, 2021)
There are few validated scales for police legitimacy, and the ambiguous dimensionality of legitimacy raises a serious issue. This study tests a multidimensional scale of legitimacy, drawing upon the police legitimacy model. To identify a certain number of classes with a similar pattern of hypothesized legitimacy among a nationally representative sample of South Korean adults, we employed latent class analysis that legitimacy researchers have yet to consider. The current study found that police legitimacy was constituted with the four sub-dimensions of lawfulness, procedural fairness, police effectiveness, and equitable distribution of police sanctions. South Korean adults within the four multidimensional legitimacy scales were separated into three clusters: the legal procedure-oriented group (41.6%), the equitable sanction-oriented group (20.8%), and the cynic-oriented group (37.6%). The odds of self-reported complying with police requests and cooperating with the police were higher among members in both the legal procedure-oriented and equitable sanction-oriented groups compared to those in the cynic-oriented group. Finally, the four multidimensional legitimacy scales had a direct effect on both self-reported compliance and cooperation and had a mediating effect on the relationship between obligation to obey and both outcome variables. We conclude that police in South Korea should enhance the four multidimensions of legitimacy during each encounter with the public.